2012
DOI: 10.1523/jneurosci.2660-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

That's Near My Hand! Parietal and Premotor Coding of Hand-Centered Space Contributes to Localization and Self-Attribution of the Hand

Abstract: The ability to identify and localize our own limbs is crucial for survival. Indeed, the majority of our interactions with objects occur within the space surrounding the hands. In non-human primates, neurons in the posterior parietal and premotor cortices dynamically represent the space near the upper limbs in hand-centered coordinates. Neuronal populations selective for the space near the hand also exist in humans. It is unclear whether these remap the peri-hand representation as the arm is moved in space. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
248
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(286 citation statements)
references
References 76 publications
37
248
1
Order By: Relevance
“…Petkova and colleagues suggest that clusters of activation in the vPMc (and the PPc) reflect a homologous multisensory integration system in the human brain, in agreement with previous neuroimaging evidence (Bremmer et al, 2001;Brozzoli, Gentile, Petkova, & Ehrsson, 2011;Cardini et al, 2011;Makin et al, 2007;Serino, Canzoneri, & Avenanti, 2011). In addition, other studies from the same group suggested that multisensory integration in the vPMc is not only involved in the multisensory integration of body-related stimuli, but is also responsible for illusory ownership of body parts (Brozzoli, Gentile, & Ehrsson, 2012;Ehrsson, Holmes, & Passingham, 2005;Ehrsson, Spence, & Passingham, 2004;Makin, Holmes, & Ehrsson, 2008). In an fMRI version of the RHI, Ehrsson showed that vPMc activity was stronger during synchronous than asynchronous visuo-tactile stimulation, was also stronger when subjects started experiencing the illusion, and was positively correlated with the strength of the illusion measured by questionnaires (Ehrsson et al, 2004; see also Ehrsson et al, 2005).…”
Section: Neural Bases Of Whole-body Ownership and Self-locationsupporting
confidence: 70%
See 1 more Smart Citation
“…Petkova and colleagues suggest that clusters of activation in the vPMc (and the PPc) reflect a homologous multisensory integration system in the human brain, in agreement with previous neuroimaging evidence (Bremmer et al, 2001;Brozzoli, Gentile, Petkova, & Ehrsson, 2011;Cardini et al, 2011;Makin et al, 2007;Serino, Canzoneri, & Avenanti, 2011). In addition, other studies from the same group suggested that multisensory integration in the vPMc is not only involved in the multisensory integration of body-related stimuli, but is also responsible for illusory ownership of body parts (Brozzoli, Gentile, & Ehrsson, 2012;Ehrsson, Holmes, & Passingham, 2005;Ehrsson, Spence, & Passingham, 2004;Makin, Holmes, & Ehrsson, 2008). In an fMRI version of the RHI, Ehrsson showed that vPMc activity was stronger during synchronous than asynchronous visuo-tactile stimulation, was also stronger when subjects started experiencing the illusion, and was positively correlated with the strength of the illusion measured by questionnaires (Ehrsson et al, 2004; see also Ehrsson et al, 2005).…”
Section: Neural Bases Of Whole-body Ownership and Self-locationsupporting
confidence: 70%
“…In an fMRI version of the RHI, Ehrsson showed that vPMc activity was stronger during synchronous than asynchronous visuo-tactile stimulation, was also stronger when subjects started experiencing the illusion, and was positively correlated with the strength of the illusion measured by questionnaires (Ehrsson et al, 2004; see also Ehrsson et al, 2005). In line with this view, a recent neuroimaging study revealed that vPMc neurons, which normally respond to visual stimuli presented close to the hand, also respond to visual stimuli presented close to a fake hand, but only after a sense of ownership for the fake hand has been induced through the RHI (Brozzoli, Gentile, & Ehrsson, 2012). The claim that Petkova et al (2011) make that similar multisensory integration mechanisms in the vPMc are responsible for the experience of a whole body as one's own, follows this research trend.…”
Section: Neural Bases Of Whole-body Ownership and Self-locationmentioning
confidence: 60%
“…In addition, both subjects spontaneously reported that the sensation originated from the rubber hand in the illusion condition, which is equivalent to the referral of touch phenomenon observed in the classical rubber hand illusion (3). Previous studies have shown that the integration of visual and tactile signals in multisensory brain regions is a key mechanism for generating ownership of a seen limb (10,18). Our findings therefore support a flexible model of multisensory integration for bodily self-attribution (8,(12)(13)(14), which allows for low-fidelity artificial sensory feedback to be merged with visual signals from a limb-like object being touched as long as the stimuli are spatially and temporally matched.…”
Section: Discussionsupporting
confidence: 52%
“…This is consistent with earlier electrophysiological evidence from monkeys and neuroimaging evidence from humans that have implicated active neuronal populations in the posterior parietal cortex as well as the ventral premotor cortex, which is anatomically connected to this parietal region, in the formation of a central multisensory representation of the limb in space (9-12, 50, 51). Interestingly, these areas are active during the RHI (9, 10, 52), and there is a correlation between the shift in perceived hand position toward the rubber hand and neural responses in the posterior parietal cortex indexing a shift in (peri-)hand space toward the rubber hand (52). Information from the posterior parietal representation of one's own hand in space could reach the cerebellum-where forward models are likely situated (26,40,41)-through the anatomical connections between these structures (53,54).…”
Section: Discussionmentioning
confidence: 99%